2013
DOI: 10.2528/pier13011710
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Shielding of Underground Cable Duct Banks

Abstract: Abstract-In this paper an in-depth parametric analysis of shielding effectiveness obtained when using ferromagnetic or conductive screens to mitigate the field generated by duct banks is presented. Due to the need of a case-by-case approach, all the simulations, performed by a finite element software (GetDp), are applied to a case study composed by 9 (3 × 3) ducts, with six of them including high voltage single-core cables and the three left empty for eventual future expansion. Two shielding geometries are tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The electric transmission lines and distribution networks generate an important low-frequency magnetic field, which greatly necessitates the development of magnetic field mitigation procedures by minimizing the intensities in the sensitive zone with the shield technique [36]- [37].…”
Section: Mitigation Of Magnetic Field By Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric transmission lines and distribution networks generate an important low-frequency magnetic field, which greatly necessitates the development of magnetic field mitigation procedures by minimizing the intensities in the sensitive zone with the shield technique [36]- [37].…”
Section: Mitigation Of Magnetic Field By Shieldingmentioning
confidence: 99%
“…The passive compensation technique is very simple, and has a low impact ampacity and a low cost [37]- [39].…”
Section: Mitigation Of Magnetic Field By Shieldingmentioning
confidence: 99%
“…The use of metallic shields is one of the passive solutions presented earlier and has been extensively used on its own, or in combination with other mitigation systems, for mitigating the MF in buildings close to OHL [13] and in the mitigation of the MF generated by UPC [38,71,72,[89][90][91] and MV/LV substations [92][93][94][95]. In literature in the last decades, different geometries have been proposed and analyzed concerning their application for electrical applications, employing conductive and/or ferromagnetic materials [25,38,91,[94][95][96][97][98][99]. Thus, for each shield geometry and for a particular location, a number of parameters must be specified for ensuring the required MF mitigation (shield dimensions, position relative to the source, and material properties).…”
Section: Passive Shieldsmentioning
confidence: 99%
“…However, few studies can be found regarding the optimization of magnetic shields applied to power systems. Thus, for power installations, most of the studies have tackled this problem by means of parametric analyses [25,38,90,91,96,98], where the main conclusions highlight that better a mitigation performance is obtained when the shield is larger and closer to the MF source. However, in some situations, like UPC, the closer the shield the higher the induced losses and, hence, the temperature.…”
Section: Passive Shieldsmentioning
confidence: 99%